Risk of dementia in patients with toxoplasmosis: a nationwide, population-based cohort study in Taiwan - Yang, Hung-Yi; Chien, Wu-Chien; Chung, Chi-Hsiang; Su, Ruei-Yu; Lai, Chung-Yu; Yang, Chuan-Chi; Tzeng, Nian-Sheng (Parasites & vectors, 2021)
Background Approximately 25–30% of individuals worldwide are infected with Toxoplasma gondii ( T. gondii ), which is difficult to detect in its latent state. We aimed to evaluate the association between toxoplasmosis, the risk of dementia, and the effects of antibiotics in Taiwan. Methods This nationwide, population-based, retrospective cohort study was conducted using the Longitudinal Health Insurance Database containing the records of 2 million individuals retrieved from Taiwan’s National Health Insurance Research Database. Fine–Gray competing risk analysis was used to determine the risk for the development of dementia in the toxoplasmosis cohort relative to the non-toxoplasmosis cohort. A sensitivity analysis was also conducted. The effects of antibiotics (sulfadiazine or clindamycin) on the risk of dementia were also analyzed. Results We enrolled a total of 800 subjects, and identified 200 patients with toxoplasmosis and 600 sex- and age-matched controls without toxoplasmosis infection in a ratio of 1:3, selected between 2000 and 2015. The crude hazard ratio (HR) of the risk of developing dementia was 2.570 [95% confidence interval (CI) = 1.511–4.347, P < 0.001]. After adjusting for sex, age, monthly insurance premiums, urbanization level, geographical region, and comorbidities, the adjusted HR was 2.878 (95% CI = 1.709–4.968, P < 0.001). Sensitivity analysis revealed that toxoplasmosis was associated with the risk of dementia even after excluding diagnosis in the first year and the first 5 years. The usage of sulfadiazine or clindamycin in the treatment of toxoplasmosis was associated with a decreased risk of dementia. Conclusions This finding supports the evidence that toxoplasmosis is associated with dementia and that antibiotic treatment against toxoplasmosis is associated with a reduced risk of dementia. Further studies are necessary to explore the underlying mechanisms of these associations. Graphical Abstract